Lower Plasma Total Testosterone Levels Were Associated With Steeper Decline in Brain Glucose Metabolism in Non-demented Older Men - Wang, Xiwu; Lv, Zhaoting; Wu, Qian; Liu, Huitao; Gu, Yanrou; Ye, Teng (Frontiers in Aging Neuroscience, 2021)
Objective: There is growing evidence that testosterone may be implicated in the pathogenesis of Alzheimer’s disease. We aimed to examine the relationship between plasma total testosterone levels and change in brain glucose metabolism over time among non-demented older people. Methods: The association of plasma total testosterone levels and change in brain glucose metabolism among non-demented older people was investigated cross-sectionally and longitudinally. Given a significant difference in levels of plasma total testosterone between gender, we performed our analysis in a sex-stratified way. At baseline, 228 non-demented older people were included: 152 males and 76 females. Results: In the cross-sectional analysis, no significant relationship between plasma total testosterone levels and brain glucose metabolism was found in males or females. In the longitudinal analysis, we found a significant association of plasma total testosterone levels with change in brain glucose metabolism over time in males, but not in females. More specifically, in males, higher levels of total testosterone in plasma at baseline were associated with slower decline in brain glucose metabolism. Conclusion: We found that higher levels of total testosterone in plasma at baseline were associated with slower decline in brain glucose metabolism in males without dementia, indicating that testosterone may have beneficial effects on brain function.